The exantric-consantric laser catheter for in-stent restenosis - Ilkay, E; Karaca, I; Özbay, Y; Kilicoglu, E; Akbulut, M; Özdag, Z; Aslan, N (Medimond S R L, 2000)
Excimer laser is a suggested debulking procedure for diffuse in stent restenosis. We aimed to evaluate the effectiveness and reliability of consentric-eccentric catheter usage in the same lesion In this study 2 female, male patients, whose mean age were 56+/-9 years and length of in-stent restenosis was 10 mm (Mean 14+/-7 mm), evaluated. Width of stent was 3 mm in 7 patients and 3.5 mm in 3 patients. First 1.7C then 1.7E laser catheter was used for the same patients. MLD by QCA were measured before and after each procedure. After the procedure, troponin T was measured cardiac troponin T quantitative (Roche) system. Q wave, nonQwave myocardial infarction, urgent CABG and death were enrolled. Kolmoporow test was used for distribution suitability and than paired-t test was applied. P<0.05 were accepted statistically significant. Troponin levels were negative in all patients. Major complications were not observed in any patient. Mean MLD was 0.56+/-0.28 mm before procedure, 1.13+/-0.31 mm after 1.7C and 1.69+/-0.35 mm after 1.7E, the p value was 0.007 between consantric and eccentric catheters. In conclusion eccentric laser catheteris a reliable method in diffuse in-stent restenosis and has higher luminal diameter gain than consantric catheter.
3rd International Congress on Coronary Artery Disease -- OCT 02-05, 2000 -- LYON, FRANCE
Keywords: Angioplasty; Saline; Trial